About special attributes of military disciplinary and legal coercion - Cheshka, Uladzimir Y. (Journal of the Belarusian State University. Law, 2019)
The article considers disciplinary and legal coercion of the military like a type of a state and legal coercion as well as its features. Affiliation of disciplinary and legal coercion of the military with branch of administrative law is noted. Eight special attributes of military disciplinary and legal coercion are determined on the basis of features of disciplinary and legal coercion and analysis of the regulations that govern military service.
Keywords: disciplinary and legal coercion; military service; military; special attributes